An innovative approach for enhancing capacity utilization in point-to-point voice over internet protocol calls - M. Abualhaj, Mosleh; Abu-Shareha, Ahmad Adel; Al-Khatib, Sumaya Nabil; O. Hiari, Mohammad; Al-Mahadeen, Layth (International Journal of Electrical and Computer Engineering (IJECE), 2024)
Voice over internet protocol (VoIP) calls are increasingly transported over computer-based networking due to several factors, such as low call rates. However, point-to-point (P-P) calls, as a division of VoIP, are encountering a capacity utilization issue. The main reason for that is the giant packet header, especially when compared to the runt P-P calls packet payload. Therefore, this research article introduced a method to solve the liability of the giant packet header of the P-P calls. The introduced method is named voice segment compaction (VSC). The VSC method employs the unneeded P-P calls packet header elements to carry the voice packet payload. This, in turn, reduces the size of the voice payload and improves network capacity utilization. The preliminary results demonstrated the importance of the introduced VSC method, while network capacity improved by up to 38.33%.